Basic Income Reform in Germany: Better Gradualism than Cold Turkey - Alexander Spermann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper advocates the cautious and constitutional evolution of existing basic income schemes (?unemployment benefit II?) and Targeted Negative Income Tax (TNIT = "Einstiegsgeld") into a means-tested combi-wage model for the future long-term unemployed (gradualism strategy). The paper argues that, with regard to existing unemployment benefit II claimants, stronger financial incentives should be offered on a time restricted basis by largely disregarding (up to the relative poverty line) earnings from "mini", "midi" and part-time jobs – with the aim of providing current unemployment II claimants with a powerful incentive to work at least 15 hours a week and thus to relinquish their unemployed status. Bearing in mind the uncertain employment impact and the related fiscal risks, the paper advises against additional financial incentives by reducing support levels from one day to the next (cold turkey strategy).
Keywords: I38; J22; 330; Labor Market Reform; Employee Subsidy; Workfare; longterm unemployment